Patients' Needs Regarding Work-Focused Healthcare: A Qualitative Evidence Synthesis. - Hagendijk, Marije E.; Zipfel, Nina; Melles, Marijke; van der Wees, Philip J.; Hulshof, Carel T. J.; Zwaan, Elmi; van der Burg-Vermeulen, Sylvia J.; Hoving, Jan L. (Journal of Occupational Rehabilitation, 2025)
Purpose: To identify, appraise, and synthesize qualitative research evidence exploring patients' needs regarding work-focused healthcare. Methods: A systematic review was conducted in accordance with the PRISMA statement guidelines to identify studies reporting patients' needs regarding work-focused healthcare. Four databases (MEDLINE, Embase, PsychInfo and Web of Science) were systematically searched from January 2000 until May 2023 and screened in duplicate by pairs of two reviewers. Inclusion criteria were qualitative data collection method, and patients' perspectives regarding healthcare focusing on work when experiencing work-related problems due to chronic medical conditions. Data extraction and synthesis was executed by means of an inductive thematic analysis approach. The quality of the included studies was assessed using the CASP Qualitative Study checklist. Confidence in the review findings was assessed through the Confidence in the Evidence from Reviews of Qualitative research (CERQual) approach. Results: Out of 23,677 records, 97 qualitative studies were included. Needs regarding four main themes were identified: (1) Substantive guidance, which comprises the specific content of work-focused healthcare; (2) Clear and continuous process, which comprises clarification and optimization of the work-focused healthcare process; (3) Supportive attitude and behavior, which comprises a positive and supportive attitude and behavior from professionals towards the patients; and (4) Tailored approach, which comprises the delivery of tailored care to the individuals' needs. 17 subthemes were identified. Conclusion: The broader insight in patients' needs in work-focused healthcare can help (occupational) healthcare professionals adopt a more patient-centred approach in practice.